Prepartum maternal supplementation of Capsicum oleoresin improves colostrum quality and buffalo calves' performance - An, Zhigao; Abdelrahman, Mohamed; Zhou, Jiayan; Riaz, Umair; Gao, Shanshan; Gao, Shan; Luo, Gan; Yang, Liguo (Frontiers in Veterinary Science, 2022)
The present study aims to evaluate the effects of prepartum maternal supplementation of Capsicum oleoresin (CAP) on colostrum quality and growth performance in newborn buffalo calves. Twelve multiparous buffaloes were randomly assigned to two groups starting from 4 weeks prepartum: the control group with a basal diet (CON) and the treatment group with a basal diet supplemented with 20 mg CAP/kg dry matter (CAP20). After birth, all calves were weighed and received colostrum from their respective dam directly within 2 h. After that, calves received pasteurized milk and starter feed till 56 days of age. The results showed that CAP increased lactose (P < 0.05) in colostrum, and it tended to increase monounsaturated fatty acids; however, it decreased colostrum urea nitrogen (P < 0.10). CAP did not affect colostrum yield and immunoglobulin G and M concentrations. The weekly starter intake was not affected by maternal CAP supplementation during the first 6 weeks of life. There was an increasing tendency in weekly starter intake from weeks 7 and 8 (P < 0.10) in CAP20 compared with CON. At 7 days of age, calves in CAP20 had higher immunoglobulin G (P < 0.05) and a decreased tendency in calves' serum glucose compared with CON. Additionally, maternal CAP supplementation increased calves' serum β-hydroxybutyric acid (P < 0.05) and tended to increase total protein (P < 0.10), while decreased non-esterified fatty acids (P < 0.05) at 56 days of age. Calves in CAP20 had higher final withers height, final heart girth, average withers height, and average heart girth than the CON (P < 0.05). These results suggest that maternal CAP supplementation could improve colostrum quality and positively affect the performance of buffalo calves.